PENAMBAHAN TEPUNG DAGING GURITA PADA PAKAN PELET KOMERSIL TERHADAP PERTUMBUHAN IKAN LELE (Clarias sp.) - Nurifansyah, Nurifansyah; Marzuki, Muhammad; Diniarti , Nanda (Journal of Fish Nutrition, 2024)
Catfish is a freshwater commodity often found in traditional and modern markets. Cultivation is also carried out in almost all regions, but the obstacle is feed availability. Therefore, we are looking for feed ingredients that are widely available and capable of increasing catfish growth quickly. Octopus is a fishery commodity abundant in certain seasons and requires processing so that it is not wasted. Octopus can be made into meal and used as raw material for catfish feed. The research aimed to analyze the effect of adding octopus meal to commercial feed for the growth of catfish (Clarias sp.). This research used an experimental method with 4 treatments (P1: 100% pellets, 0% octopus (without addition), P2: 98% pellets, 2% octopus meal, P3: 96% pellets, 4% octopus meal, P4: 94% pellets, 6% octopus meal) and 3 repetitions. The results showed that the addition of octopus meal increased the growth of catfish with the best treatment, namely the P4 treatment. Adding octopus meal to commercial feed gave significant results on absolute weight growth, specific weight growth, absolute length growth, specific length growth, feed conversion ratio, and feed efficiency level but did not affect the survival rate of catfish.